DETERMINANTS OF CONSUMER PURCHASING DECISIONS IN COFFEE SHOPS: THE ROLE OF INTERIOR DESIGN, PRICE AND TASTE - Irianti, Lutvia Ragilta; Satoto, Eko Budi; Sari, Maheni Ika (Univesitas Muhammadiyah Tangerang, 2025)
Increasingly tight competition requires producers to be able to implement good management and requires the right strategy in order to maintain and develop their business such as analysis, planning and implementation to build profits. This study aims to determine and analyze the influence of interior design, price, and taste on purchasing decisions at Erenka Coffee Shop, Banyuwangi. This type of research is causality research, using quantitative methods with a sample size of 100 respondents and using non-probability sampling techniques with the Accidental Sampling and Purposive Sampling approaches, using data collection techniques in the form of questionnaires to respondents. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypothesis testing and coefficient of determination R2. based on the results of multiple linear regression analysis, it produces positive findings, meaning that if interior design, price, and taste continue to be improved, it will have an impact on purchasing decisions at Erenka Coffee Shop. The results of the t-test analysis obtained showed that interior design, price, and taste had a partial and significant influence on purchasing decisions at Erenka Coffee Shop, the results of the R2 determination coefficient test were that the level of influence contribution was 0.913 or 91%.